Isolation and characterization of the chemical constituents of Sonchus wightianus of Nepalese origin - Joshi, Susan; Poudel, Tej Narayan (Journal of Nepal Chemical Society, 2013)
Phytochemical screening of Sonchus wightianus of Nepalese origin were carried out. Phytochemical screening showed the presence of fatty acids, triterpenes, sterols, polyphenols, emodins, quinones, glycosides, polyose and anthracenosides. Compounds β-sitosterol, β-sitosterol glycoside, 1-Hexacosanol and Hexadecanoic methyl ester were isolated.1-Hexacosanol and Hexadecanoic methyl ester are isolated for the first time from Sonchus wightianus. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8119 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 115-120 Uploaded Date: May 24, 2013